Benin : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper and Statistical Appendix analyzes sources of economic growth in Benin. It concludes that the policies implemented since the early 1990s paved the way for higher growth rate by raising total factor productivity as well as capital accumulation. The paper examines the cotton sector reform in Benin and the subsidies by major producing countries. It also analyzes recent trends in Benin's external competitiveness, and conducts an analysis of the equilibrium exchange rate to assess whether the movements in the real effective exchange rate in Benin were consistent with the underlying macroeconomic fundamentals.